2007
DOI: 10.1111/j.1471-4159.2007.05129.x
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic acid prevents lipopolysaccharide‐induced cytokine production in microglial cells by inhibiting lipopolysaccharide receptor presentation but not its membrane subdomain localization

Abstract: Recognition of lipopolysaccharide (LPS), the endotoxin of gram‐negative bacteria, by microglia occurs through its binding to specific receptors, cluster of differentiation 14 and toll‐like receptor‐4. LPS binding to these receptors triggers the synthesis of proinflammatory cytokines that coordinate the brain innate immune response to protect the CNS of the infection. Docosahexaenoic acid (DHA), a n‐3 polyunsaturated fatty acid highly incorporated in the brain, is a potent immunomodulator. In this study, we inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
92
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(111 citation statements)
references
References 64 publications
14
92
1
Order By: Relevance
“…Because LiCl did not increase the concentration of its precursor, unesterified DHA, or iPLA 2 -VI activity, consistent with prior data ( 20,33 ), the increment may have arisen from enhanced 15-LOX activity. On the other hand, unesterified DHA likely is partitioned in different brain compartments [it is found in neurons and glia ( 41,42 )], as reported for unesterified AA ( 23 ), one of which may be the precursor to 17-OH-DHA. Increased 15-LOX activity is suggested by the increased 15-HETE in the rats fed the LiCl diet during high LPS exposure, because 15-HETE is generated from AA by the action of 15-LOX.…”
Section: Eicosanoidsmentioning
confidence: 93%
“…Because LiCl did not increase the concentration of its precursor, unesterified DHA, or iPLA 2 -VI activity, consistent with prior data ( 20,33 ), the increment may have arisen from enhanced 15-LOX activity. On the other hand, unesterified DHA likely is partitioned in different brain compartments [it is found in neurons and glia ( 41,42 )], as reported for unesterified AA ( 23 ), one of which may be the precursor to 17-OH-DHA. Increased 15-LOX activity is suggested by the increased 15-HETE in the rats fed the LiCl diet during high LPS exposure, because 15-HETE is generated from AA by the action of 15-LOX.…”
Section: Eicosanoidsmentioning
confidence: 93%
“…Our study and current literature cannot resolve these issues but might serve as a starting point for research on proand anti-infl ammatory effects of prostaglandins. Moreover, whether the effect of 3 FA is on CD14, TLR4 or other parts of the receptor system for LPS or downstream remains to be settled ( 40 ).…”
Section: Tnf-␣ Il-1 ␤ Il-6 and G-csf Releasementioning
confidence: 99%
“…Both in vivo and in vitro studies have reported antiinflammatory activities of DHA in the brain especially in microglia (Laye, 2010;Orr and Bazinet, 2008). At the cellular level, brain DHA modulates several proinflammatory signalling pathways in microglia such as TLR signalling and nucleotide-binding oligomerization domain protein (NOD) signalling (De Smedt-Peyrusse et al, 2008;Liu et al, 2012), inhibits JUNK , and reduces or blocks NF-kB signalling (De Smedt-Peyrusse et al, 2008;Orr et al, 2013). The inhibitory effect of DHA on proinflammatory signalling pathway could be mediated by both non-genomic and genomic effect.…”
Section: How Do N-3 Pufa Mechanisms Control Neuroinflammation?mentioning
confidence: 99%
“…The inhibitory effect of DHA on proinflammatory signalling pathway could be mediated by both non-genomic and genomic effect. Indeed, DHA influences membrane composition of microglial cells and the TLR4 positioning, decreasing the binding of its ligand LPS (De Smedt-Peyrusse et al, 2008). DHA also impairs the phospholipid raft assembly of EPA and DHA in the plasma membrane (Rockett et al, 2011;Ruth et al, 2009).…”
Section: How Do N-3 Pufa Mechanisms Control Neuroinflammation?mentioning
confidence: 99%
See 1 more Smart Citation